Three-body bound states in dipole-dipole interacting Rydberg atoms. - Kiffner, M; Li, W; Jaksch, D (2013)
We show that the dipole-dipole interaction between three identical Rydberg atoms can give rise to bound trimer states. The microscopic origin of these states is fundamentally different from Efimov physics. Two stable trimer configurations exist where the atoms form the vertices of an equilateral triangle in a plane perpendicular to a static electric field. The triangle edge length typically exceeds R≈2 μm, and each configuration is twofold degenerate due to Kramers degeneracy. The depth of the potential wells and the triangle edge length can be controlled by external parameters. We establish the Borromean nature of the trimer states, analyze the quantum dynamics in the potential wells, and describe methods for their production and detection.